Learners awareness of HIV/AIDS and their attitudes towards peer educators in Khayamandi High School - Booi, Faith Nontuthuzelo (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.